Impact of β-thalassemia trait carrier state on inflammatory status in patients with newly diagnosed hypertension. Issue 5 (May 2019) - Triantafyllou, Athanasios I.; Farmakis, Dimitrios T.; Lampropoulos, Konstantinos M.; Karkalousos, Petros L.; Triantafyllou, Epameinondas A.; Papingiotis, Georgios; Megalou, Aikaterini; Karpanou, Eva A.
Abstract : Background: B-thalassemia carrier state or thalassemia minor confers cardiovascular protection through favorable lipidemic and blood pressure profile. However, its impact on inflammatory status—a common denominator of the above conditions—has not been addressed. Methods: We investigated a wide range of inflammatory markers [white blood cell (WBC) count, homocysteine, C-reactive protein (CRP), serum amyloid A (SAA), fibrinogen, plasminogen, fibronectin, plasminogen activator inhibitor-1 (PAI-1), and uric acid] in a large cohort of 15 805 newly diagnosed hypertensive patients (8299 men, 7506 women); 626 of them (4.0%) had thalassemia minor. Results: The levels of WBC, homocysteine, CRP, SAA, fibrinogen, and PAI-1 were significantly lower in thalassemia minor patients, but not of plasminogen, fibronectin, and uric acid. In multivariate linear regression analyses, the lower values of WBC (<0.001), CRP (<0.001), homocysteine (<0.001), fibrinogen (<0.001), and PAI-1 (0.008), but not of SAA, were independently associated with thalassemia minor. The interaction between thalassemia minor and body mass index had a significant impact only on WBC and CRP ( P for the interaction 0.010 and 0.005, respectively), whereas the interaction between thalassemia minor and sex had a significant impact only on fibrinogen ( P for the interaction 0.007). Conclusion: Thalassemia minor is followed by a favorable inflammatory profile that may contribute to the overall better cardiovascular health of the carriers.